German and Italian validation of the Dyadic Coping Inventory-Sexual Minority Stress (DCI-SMS) scale - Randall, Ashley K.; Liekmeier, Esther; Totenhagen, Casey J.; Lannutti, Pamela J.; Leon, Gabriel A.; Siegel, Magdalena; Ditzen, Beate; Baiocco, Roberto; Chiarolanza, Claudia; Meuwly, Nathalie; Zemp, Martina; Fischer, Melanie S.; et al. (Journal of family psychology, 2024)
Lesbian, gay, bisexual, and transgender individuals (hereafter people with minoritized sexual orientation and/or gender identities) have limited legal rights and access to resources because of their marginalized status in society. These limitations are associated with notable health disparities and increase experiences of minority stress. For those in a romantic relationship, being able to communicate and cope with one’s partner-dyadic coping-can help buffer stress’ deleterious effects on well-being. Given the promise of understanding how dyadic coping can mitigate experiences of sexual minority stress, the Dyadic Coping Inventory-Sexual Minority Stress (DCI-SMS) was recently created and validated with those living in the United States to assess how partners cope with sexual minority stress. Answering a global call to expand psychological science beyond a U.S. centric perspective, the purpose of this study was to validate the DCI-SMS in German and Italian using samples from Austria, Germany, Switzerland, and Italy, respectively. Confirmatory factor analysis results, along with tests of convergent and discriminant validity, and measurement invariance, suggest that the DCI-SMS is a valid measure of stress communication and dyadic coping behaviors for those in a same-gender relationship in the countries sampled. Important future directions include examining its efficacy in other countries, such as those with more adverse sociopolitical climates for people with minoritized sexual orientation and/or gender identities in a same-gender relationship. Limitations and future directions for research and clinical practice are presented. (PsycInfo Database Record (c) 2024 APA, all rights reserved)
Gesehen am 24.06.2025